Psychological Predictors of Perceived Age and Chronic Pain Impact in Individuals With and Without Knee Osteoarthritis. Issue 8 (August 2020) - Booker, Staja Q.; Sibille, Kimberly T.; Terry, Ellen L.; Cardoso, Josue S.; Goodin, Burel R.; Sotolongo, Adriana; Staud, Roland; Redden, David T.; Bradley, Laurence A.; Fillingim, Roger B.; Bartley, Emily J.
Abstract : Objective: Chronological age is a risk factor in chronic pain; however, aging research supports the premise that physical and psychological health may better predict perceived age. Given the lack of evidence on perceived age in the context of chronic pain, the current study presents novel findings about the relationship between perceived age, chronic pain impact, and psychological function in adults with and without knee osteoarthritis. Methods: This secondary analysis was part of an ongoing multisite observational cohort study to understand the progression of knee pain and disability. Community-dwelling adults (N=227) ages 45+ completed measures of trait resilience, trait positive and negative affect, pain catastrophizing, subjective perceptions of age, and the Graded Chronic Pain Scale. Results: On average, participants reported feeling 10 years younger than their chronological age; however, this effect was attenuated in individuals reporting high-impact pain. Lower perceived age was associated with lower pain impact (low pain/low disability), while higher perceived age correlated with higher pain impact (high pain/high disability) and more adverse psychological effects. Using hierarchical linear regression, high-impact pain and positive affect emerged as statistically significant predictors of perceived age, whereas no differences were observed among trait resilience, negative affect, or pain catastrophizing. Discussion: These findings highlight the importance of a biopsychosocial approach in understanding the intersection between psychological and physical factors associated with chronic pain. Addressing negative self-perceptions of aging, while simultaneously augmenting positive affect, through psychological therapies may mitigate pain and disability.